(untitled) (Kinesiology, 2019)
Although it is well established that velocity is an important factor in the success in ball sports and the presence of opposition influences it, there has been no research done to date on the ball velocity in padel shots. The overhead smash is one of the most successful shots in this sport, and the present study aimed to study the effect of opposition on smash performance in semi-professional and amateur padel players. 44 semi-professional (n=14) and amateur (n=30) players volunteered to participate in this study. The overhead smash velocity was recorded for both groups of players with and without opposition using a radar gun. The ball velocity decreased in both groups of players in the presence of opposition (p < 0.001), although the semi-professional players had a greater velocity in both situations (p < 0.001) compared to amateurs and the reduction of velocity in the presence of opposition was greater in the amateurs (p < 0.001). The greater velocities for the semi-professional padel players could be attributed to a technical and tactical superiority owing to greater experience and higher level of competition. Simulating conditions of opposition could help reduce the velocity-precision trade-off, helping the players increase their overhead smash velocities.